Propuesta de modelo logístico para el transporte y distribución del queso de hoja de los productores de los municipios de El Espino y Güicán (2023)
This project was developed in the área of El Espino and Güicán in the Nort of Boyacá. The main objective of this project is to establish a proposed logistical model for the transportation and distribution of leafy cheese from producers located in these municipalities, for wich it uses a descriptive methodology and classified as mixed because it uses quantitative data that describes the composition of means of transportation and the possibility of implementig improvements aimed at the profitability of the logis tics proces, for artesanal producers.